Effect of Soil Moisture on Vibration Detection Using an ESP32-Based IoT System - Kisman Akuba; Dewa Gede Eka Setiawan; Muhammad Yunus; Septiana Kurniasari; Icha Untari Meidji; Abd. Wahidin Nuayi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Earthquakes are natural disasters that frequently occur due to inadequate soil structure and varying soil moisture conditions, which significantly influence ground vibration characteristics. This study aims to investigate the effect of soil moisture conditions, specifically dry and wet soil on vibration response. The system employs an SW-420 vibration sensor integrated with an ESP32 microcontroller for data acquisition and real-time monitoring. The experiment was conducted on a small-scale soil medium, with vibration data recorded at one-second intervals for a duration of 60 seconds. The measured vibration signals were transmitted and monitored in real time, then analyzed to determine which soil condition exhibits greater vibration damping characteristics. The results indicate that soil moisture has a significant effect on the vibration sensor response. The highest average ADC value was obtained in dry soil at 823.21, while wet soil produced a lower average ADC value of 533.16. The decrease in ADC values demonstrates increased vibration damping as soil water content increases. These findings confirm that higher soil moisture enhances energy absorption and reduces vibration transmission. Therefore, the IoT-based vibration detection system using the ESP32 and SW-420 sensor is capable of distinguishing soil vibration characteristics under different moisture conditions and shows strong potential for further development as an early warning system for landslide mitigation.